Sullied: The Albanian Student Movement of December 1990 - Shahini, Arjan (Frontiers in Political Science, 2021)
The study analyzes the beginning of the Albanian student movement of December 1990 from a historical–sociological and comparative perspective. This historical interpretation of various sources (newspaper articles, activists’ memoirs, interviews, and archival documents) draws its theoretical arguments from social movement studies, student activism, and the sociology of higher education. The study offers a complex explanation of the role of the movement during the country’s democratic transition by also looking at similar cases. Considerations of the broader international and local implications, the role of the university, the academic staff, and the student organization all are accounted for. After tracing the repertoires of strategies and content of the movement to the Albanian Cultural Revolution of the 1960s, the study argues that student activism benefitted from the structural opportunities provided by changes introduced in higher education during the historical sequence of late Socialism.